Talking with the neighbours: Understanding spatial accommodation during plant development - (:unkn) unknown (My University, 2025)
Turgor-driven pressure of plant cells can be higher than that of a car tire. It puts tremendous forces onto cell walls and drives changes in cell shape. This has driven unique mechanisms to control organ formation in comparison to metazoans. The fascinating interplay between forces and local cellular reorganization is poorly understood. Growth of lateral roots is a prominent example of a developmental process in which mechanical forces are generated. Lateral roots grow from a single cell layer that resides deep within the primary root. On its way out, lateral roots grow through endodermal, cortical and epidermal cell layers. I recently demonstrated that endodermal cells actively accommodate lateral root formation. Responses include a dramatic volume loss and a controlled degradation of their lignin-based paracellular diffusion barrier. Interfering genetically with these accommodating responses in the endodermis completely blocks cell proliferation in the pericycle. The lateral root system provides a unique opportunity to elucidate the molecular and cellular mechanisms underlying spatial accommodation in plant development. I will combine genetic screens, state-of-the-art transcript profiling and advanced microscopy to identify the molecular players and mechanisms regulating spatial accommodation. Beyond its importance for lateral root formation, this research can provide fundamental new insights into many other developmental processes that heavily depend on spatial accommodation by surrounding tissue. These include the growth of pollen tubes and infection threads, the development of sclerenchyma fibre cells or the intracellular accommodation of symbionts.
Keywords: mechanical constraints; organ initiation; Arabidopsis thaliana; cell volume regulation; lateral roots; spatial accommodation; intercellular communication